Pengelolaan Kegiatan Pengabdian Masyarakat dengan Sistem Informasi Manajemen - Made Adi Baskara Joni, I Dewa; Permana, I Putu Hendika (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 8, No. 2 Agustus 2017, 2017)
CCommunity service activities is one activity that takes the role of Information Technology (IT). IT utilization minimize the possibility of the emergence of various problems in the activities. Documents such as decrees, letters of assignment, proposals and reports of activities is often inconsistent. In the evaluation of the activities also has many limitations. If the required information such as who the lecturer is involved in the activities, how much total cost for each activity or completely very hard to know. A system built to help manage community service activities (CS) both institutional and group of lecturers CS. Users can manage at the beginning of each submission period CS activity. When necessary administrative documents such as decree and Letter of Assignment, can be generated automatically from the system. The proposal documents, reports and documentation of evidence can be uploaded into the system in order to be archived digitally and structured. The system is expected to be a solution of the problems experienced. With the new system, human error can be minimized and management activities can be done more easily with the help of IT.